Evaluaiting the Institutional Effectiveness of BAZNAS for Poverty Alleviation in Indonesia - Muhammad Fakhrur Rasyid (Sinergi International Journal of Islamic Studies, 2025)
This study examines the institutional implementation of zakat by BAZNAS (Indonesia’s National Zakat Agency) as a strategic instrument for poverty alleviation. It explores the striking disparity between the projected national zakat potential—estimated at IDR 327 trillion annually—and its relatively low realization rate, which remains within the 4–20% range. The central research inquiry posed is: To what extent is the institutional governance of zakat under BAZNAS effective in addressing entrenched structural poverty in Indonesia? Diverging from prior research predominantly reliant on secondary data, this study presents original empirical evidence derived from in-depth interviews with high-ranking officials at BAZNAS headquarters. This research integrates Islamic Social Welfare Theory and Institutional Theory into a comprehensive evaluative framework. Utilizing a qualitative-descriptive methodology, data were gathered through documentary analysis and semi-structured interviews, and analyzed using the Miles and Huberman model—comprising data reduction, data display, and conclusion drawing. The findings reveal persistent obstacles in zakat mobilization, including non-compulsory regulatory frameworks, limited public literacy on zakat, and underdeveloped institutional capacities at the regional level. Despite BAZNAS’s efforts to establish transparent systems and integrate digital innovations, structural barriers continue to impede optimization. Productive zakat programs demonstrate potential; however, longitudinal data tracing the transformation of zakat beneficiaries (mustahik) into donors (muzakki) remain scarce. This research affirms the pivotal—yet underutilized—role of zakat as an Islamic fiscal instrument in national poverty eradication strategies. It proposes several policy recommendations: tax incentives for zakat contributors, institutional capacity-building at the regional level, national-scale digital system integration, and widespread public literacy campaigns. These insights underscore the potential of zakat to align with and accelerate the realization of Sustainable Development Goal 1: No Poverty.